Elefanten i (bede)rummet. Raciale forsvindingsnumre, stemningspolitik og idiomatisk diffraktion - Kirsten Hvenegård-Lassen (The Royal Danish Library, 2019)
The elephant in the room. Racial disappearance acts, mood politics and idiomatic diffraction summarizes a particular way of handling social and cultural problems. It is about social taboos that are affectively charged: even if everybody knows the elephant is there, they ignore it. In this article, we are grappling with disappearance acts related to race and racialization at a white-dominated Danish university. Race is simultaneously there and not there in organizational policies and practices preoccupied with governing diversity. Using a recent debate over ‘prayer rooms’ in educational institutions, we develop a methodology (‘idiomatic diffraction’) sensitive towards race and racialization in contexts dominated by whiteness. Leaning on Karen Barad, we argue that diffraction may open up a space from where light can be explored in the shadows of what Sylvia Wynter names ‘Man’s Project’.